1999
DOI: 10.1172/jci4189
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-stimulated cytoskeletal reorganization and signal transduction at focal adhesions in vascular smooth muscle cells require c-Src

Abstract: Thrombin and angiotensin II (angII) have trophic properties as mediators of vascular remodeling. Focal adhesions and actin cytoskeleton are involved in cell growth, shape, and movement and may be important in vascular remodeling. To characterize mechanisms by which thrombin and angII modulate vessel structure, we studied the effects of these G protein-coupled receptor ligands on focal adhesions in vascular smooth muscle cells (VSMCs). Both thrombin and angII stimulated bundling of actin filaments to form stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 43 publications
7
119
0
1
Order By: Relevance
“…The focal adhesion complex is a highly organized site at which the actin cytoskeleton attaches indirectly, through the proteins vinculin, paxillin, and talin, to aggregates of transmembrane heterodimeric ␣-and ␤-integrins (13). It has been shown that the activated AT 1 R stimulates focal adhesion complex formation and cytoskeletal reorganization (14).…”
mentioning
confidence: 99%
“…The focal adhesion complex is a highly organized site at which the actin cytoskeleton attaches indirectly, through the proteins vinculin, paxillin, and talin, to aggregates of transmembrane heterodimeric ␣-and ␤-integrins (13). It has been shown that the activated AT 1 R stimulates focal adhesion complex formation and cytoskeletal reorganization (14).…”
mentioning
confidence: 99%
“…Overall, it can be concluded that the induction of Cas phosphorylation by TGF-␤ is dependent on E-cadherin-mediated cell-cell interaction and independent of the cell-ECM adhesion. However, considering that a variety of the stimuli leading to the stimulation of tyrosine phosphorylation of Cas have been shown to induce a rapid increase in stress fibers and in focal adhesions (19,51,70) and that we cannot rule out the possibility that the HaCaT cells in our study may not be suitable in staining for focal plaques and F-actin, further study is required to elucidate the exact mechanism of integrin-independent Cas phosphorylation in the early event of TGF-␤ signaling.…”
Section: Discussionmentioning
confidence: 94%
“…For example, cells plated on rigid substrates have more robust adhesions than those on more flexible substrates [15][16][17], presumably because rigid substrates are more capable of resisting the contractile forces from the cell. Likewise, cells treated with agents that increase actinomyosin contractility such as Lysophosphatidic acid (LPA), thrombin, or bombesin also lead to a further increase in FA size in cells plated on rigid substrates [18,19]. This is mediated by activation of the Rho pathway, which stimulates actinomyosin contractility, leading to FA growth [20].…”
Section: Adhesion and The Development Of Tensionmentioning
confidence: 99%